The biochemical contents and antioxidant activities of four tanacetum L. taxa - Emre, Irfan; Kursat, Murat; Emre, Mustafa Yunus; Yilmaz, Okkes (Mattioli 1885, 2021)
The goal of the present study is to determine some of the biochemical compositions and antioxidant capacities of plant extracts in two endemic taxa for Turkey including T. cadmeum (Boiss.) Heywood subsp. orientale Grierson and T. nitens (Boiss. & Noe) Grierson together with T. polycephalum (L.) Sch.Bip subsp. argyrophyllum (K. Koch) Podlech, and T. parthenium (L.) Sch.Bip. The fatty acids were determined by using gas chromatography, while phenolics, lipid soluble vitamins and sterols were determined by using HPLC and radical scavenging activities, total phenolics, and FRAP were determined spectrophotometrically. It was found that Tanacetum taxa have palmitic acid (C16:0), and stearic acid (C18:0) as major saturated fatty acids and linoleic acid (C18:2 n6), alpha-linolenic acid (C18:3 n3) and oleic acid (C18:1 n9) as principal unsaturated fatty acids. It was found that Tanacetum taxa had more total unsaturated fatty acid contents (60.24 +/- 0.3%-70.54 +/- 0.29%) than saturated fatty acids and it was found that T. parthenium had the highest total essential fatty acid composition (58.65%+/- 0.59%). It was also reported that the omega6/omega3 ratio of T. cadmium subsp. orientale (8.22) differed from other taxa in this study. Also, the present study showed that Tanacetum had the lowest amount of lipid soluble vitamins. On the other hand, catechin was found to be the main polyphenolic compound in this study and it was determined that T. parthenium had the highest catechin (4479.1 +/- 5.71 mu g/mg) and total phenolic contents (324.91 +/- 2.01 mu gGAE/mg) in this study. Rutin was only determined in two endemic taxa T. cadmeum subsp. orientale (23 +/- 0.91 mu g/mg), and T. nitens (5.7 +/- 0.27 mu g/mg). Also, the naringenin, vanillic acid and caffeic acid amounts of the endemic T. cadmeum subsp. orientale and T. nitens were higher than other taxa in the study. In addition, it was determined that Tanacetum taxa had a high stigmasterol content. However, T. parthenium had a higher ergosterol content (271 +/- 2.36 mu g/mg). It was also found that T. parthenium has highest D2, alpha-tocopherol, retinol acetate, ergosterol, and stigmasterol contents among the studied taxa. In addition, the study showed that Tanacetum taxa have strong DPPH and ABTS radical scavenging activities. It was concluded that Tanacetum taxa have potent antioxidant capacity.
Keywords: Antioxidant capacity; fatty acids; lipid-soluble vitamins; phenolics; sterols; Tanacetum L.